EFFECTS OF SANGUINARINE AND CHELERYTHRINE ON THE CELL CYCLE AND APOPTOSIS - Malikova, Jana; Zdarilova, Adela; Hlobilkova, Alice (Biomedical papers, 2006)
OBJECTIVES: This review summarizes the involvement of sanguinarine and chelerythrine in cell cycle regulation and cell death in various cell lines. It is focused on their potential in the treatment of cancer.METHODS: We conducted a search of PubMed, ScienceDirect and Medline for papers on the molecular mechanisms of the biological activity of sanguinarine and chelerythrine published mainly from 1995 to 2006.RESULTS AND CONCLUSIONS: Our analysis of the published studies suggested that these alkaloids are not only good candidates for chemotherapeutic regimens but may also contribute to the development of successful immune therapies of some carcinomas due to their apoptotic potential. However, the complete signalling cascade in which sanguinarine and chelerythrine treatment induces apoptotic cell death is not yet understood. Overall, the results of recent studies suggest that sanguinarine and chelerythrine may be useful as agents in the management of cancer.
Keywords: Quaternary benzo[c]phenanthridine alkaloids/Cytotoxicity/Apoptosis/Cancer/Cell signalling/Proliferation